Current Topics in Zika - Rodriguez-Morales, Alfonso J. (IntechOpen, 2018)
Zika was an arbovirus not considered relevant until the epidemics of 2007, where in the islands of the Pacific, Yap, Micronesia, and others, and later in the Americas in 2015-2016, it created a significant public health threat. Zika is a flavivirus that has been especially important not just for the high number of cases but also for its related morbidity. In the case of adult population, multiple neurological diseases are already associated and in pregnant women because of its confirmed teratogenic capacity, leading to microcephaly as well as other central nervous system (CNS) birth defects. This book tried to update the significant epidemiological and clinical research in many aspects with a multinational perspective.